Kontribusi Gaya Kepemimpinan Atasan Dan Motivasi Berprestasi Terhadap Kinerja Pegawai Dinas Pendidikan Kota Pariaman - Sukmadewi, Randia (Jurnal Pendidikan Nasional, 2021)
Based on field observation, it indicated that the performance the employees of the Education Department in Pariaman is not optimal. This will be the worried affect in achieving of the goals of achieved this institution. Researcher suspected the leadership style of superiors and achievement motivation affects employees performance of the Education Department in Pariaman, therefore, research must be done to test its truth. This research aimed to reveal the contribution of leadership style and achievement motivation employer to employee performance of the Education Department in Pariaman. The hypothesis tested in this study were: 1) leadership style employer contribution to employee performance of the Education Department in Pariaman, 2) achievement motivation to contribute to employee performance of the Education Office in pariaman, 3) leadership style and achievement motivation employer jointly contribute to performance of the Education Department officials in Pariaman. The population was the officials of the Education Department. Total population was of more than 101 people. 55 studied of samples, taken using proportional stratified random sampling technique, considering the strata level of education and working lives. The research instrument used to collect data is the Likert questionnaire that has been tested the validity and reliability. Results of data analysis showed that leadership style contributed to the Employee Performance Superior of the Education department in Pariaman of 20,4% and Achievement Motivation contribute 9.2% Employee Performance and Superior Leadership Style and Motivation Achievement jointly contribute to the employee Performance of the Education department in Pariaman was 25.6%. Based on the results of descriptive analysis showed that, leadership style is superior, including the category, achievement motivation at appropriate category and also employee performance at appropriate category. Leadership style employer contribution and achievement motivation are two important factors that could affect the performance of employees in addition to other factors that are not negligible bias which also contribute to employee performance of the Education Department Pariaman that have not been studied in this research